Oncological and reproductive outcomes of conization combined with pelvic node evaluation in patients with early-stage cervical cancer: a systematic review and meta-analysis - Wang, Yisi; Chen, Yali; Wang, Mengyao; Qin, Zhaojuan; Zhang, Lingli; Zheng, Ai; Han, Ling (Frontiers in Oncology, 2023)
Objective: This study aims to preliminarily assess the oncological and reproductive outcomes of fertility preservation treatment using conization combined with pelvic node evaluation in young patients with early-stage cervical cancer (ECC) through meta-analysis. Methods: In this meta-analysis, we analyzed studies published in PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), International Clinical Trials Registry Platform (ICTRP), and Clinical Trials. gov that appeared in our search from inception to February 7, 2023.Results: 17 relevant studies with a total of 620 patients were included, of which 444 patients received conization combined with pelvic node evaluation. The combined pregnancy rate was 45.4%(95%CI: 0.34-0.57), the combined live birth rate was 33.9%(95%CI: 0.26-0.42), the combined miscarriage rate was 4.8% (95%CI: 0.02-0.092), the combined preterm delivery rate was 5.1% (95%CI: 0.02-0.092), and the combined recurrence rate was 1.9% (95%CI: 0.006-0.035), which did not significantly differ from that of patients who received radical surgery (OR: 0.689, 95%CI: 0.506-0.938).Conclusion: Cervical conization combined with pelvic lymph node evaluation for fertility preservation in young ECC patients can achieve oncological outcomes similar to radical surgery while improving pregnancy success rates and preserving postoperative fertility. In summary, fertility preservation treatment using cervical conization combined with pelvic lymph node evaluation may be considered as a viable option for young ECC patients with strong fertility preservation desire, resulting in better pregnancy and live birth outcomes.